2018
DOI: 10.1002/etc.4032
|View full text |Cite
|
Sign up to set email alerts
|

A standardized tritrophic small‐scale system (TriCosm) for the assessment of stressor‐induced effects on aquatic community dynamics

Abstract: Chemical impacts on the environment are routinely assessed in single-species tests. They are employed to measure direct effects on nontarget organisms, but indirect effects on ecological interactions can only be detected in multispecies tests. Micro- and mesocosms are more complex and environmentally realistic, yet they are less frequently used for environmental risk assessment because resource demand is high, whereas repeatability and statistical power are often low. Test systems fulfilling regulatory needs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Unless indicated otherwise, water columns were not mixed before sampling, and only suspended algae were measured. (Riedl et al () had shown a significant correlation between suspended and total algal concentrations.) Algal population size was determined at either 4 or 5 sampling points via in vivo fluorescence activity measurements (5 × 200‐µL subsamples) with a plate reader (Tecan Infinite 200 PRO; see settings in the Supplemental Data, Table S1) to determine the algal concentration.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Unless indicated otherwise, water columns were not mixed before sampling, and only suspended algae were measured. (Riedl et al () had shown a significant correlation between suspended and total algal concentrations.) Algal population size was determined at either 4 or 5 sampling points via in vivo fluorescence activity measurements (5 × 200‐µL subsamples) with a plate reader (Tecan Infinite 200 PRO; see settings in the Supplemental Data, Table S1) to determine the algal concentration.…”
Section: Methodsmentioning
confidence: 94%
“…The assessment of chemical effects in environmentally relevant, complex test systems has been criticised because of the sometimes high variability in the data leading to low detectable effect sizes (Hanson et al 2017) and because one of the simpler, standard data analysis methods is insensitive to effects on species of low abundance (Beketov et al 2013). Variability has differing definitions in the literature (Organisation for Economic Co-operation and Development 2005;Goodman et al 2016;Leek and Jager 2017;Riedl et al 2018); in the present study we describe differences within experiments as intratest variability, differences between experiments within the same laboratory as repeatability, and differences between experiments among laboratories as reproducibility. Stressor effects can only be distinguished statistically from natural variations when intratest variability is low and repeatability is high.…”
Section: Introductionmentioning
confidence: 99%
“…The most important feature of hydra is that they are pervasive in freshwater bodies and are comparatively easy to culture in laboratory. Thus, hydra has emerged as an aquatic environmental indicator and for small scale bioassays (Quinn et al, 2012;Riedl et al, 2018). In the context to enormous use of coragen in India, the present work was undertaken to investigate the possible illeffects, if any, of coragen on non-target aquatic species using hydra as a model system.…”
Section: International Journal Of Zoological Investigationsmentioning
confidence: 99%
“…Experiments that address contaminant effects at the community and ecosystem level can be successfully conducted in the field and with laboratory-based methodologies that are well suited for some, but not all, taxa, habitats, or communities of interest. Some experiments manipulate indigenous (e.g., a soil with its native microbial or faunal assemblage) or naturally colonized communities [98], while others utilize prescribed experimental communities in field settings [101,102] or in microcosms or mesocosms [103]. Experimental approaches offer many advantages; experimental units are usually replicable, exposure concentrations may be controlled, species composition can be manipulated, and experimental designs allow specific hypotheses to be tested.…”
Section: Indirect Effects and Experimental Studiesmentioning
confidence: 99%
“…Mesocosm experiments are becoming more common and are being conducted on a wide array of taxa, including microbes [106] and in terrestrial and soil communities [107], as well as with newly created chemicals of potential concern [108]. Even mesocosm studies that are based on simplistic, tri-trophic communities, e.g., in freshwater pelagic systems [4,103], have proven successful to elucidate the mechanisms and strength of indirect effects [60]. More complex experimental ecosystems have been implemented over time that, for example, include aquatic plants and benthic invertebrates [100], increasing the ecological realism of experimental tests.…”
Section: Indirect Effects and Experimental Studiesmentioning
confidence: 99%